Comparative Study on the Prevalence of Self-medication Practices Using Antibiotics among the Different Socio-economic Classes of Shimoga, Karnataka - Sijin Wilson; Raghavendraswamy Koppad; Kanchana Nagendra; Sakshi Kumari; C. Liana; Mageppa Mandi; Ceethal Anna Joseph (Journal of Medical Evidence)
Background: Self-medication is the use of medicinal products without prior medical consultation or medical advice. Self-medication is an irresponsible use of antibiotics and contributes to the development of resistance in bacteria. This study would help to design a line of action to ameliorate the alarming trends of self-medication with antibiotics and antibiotic resistance. Aims: The objective is to assess the prevalence and patterns of the practice of self-medication using antibiotics among the general population of Shimoga district of Karnataka. Patients and Methods: A community-based cross-sectional study was carried out in the Shimoga district of Karnataka. Data were collected from 800 adults by door-step interview using a questionnaire after obtaining consent. Data were entered in Excel and were analysed using Epi-info software. Results: Of the 800 respondents, 13.5% were involved in the practice of self-medication. Of this 13.5%, 55.56% belonged to an urban area and 54.63% belonged to below the poverty line. The major source of non-prescription antibiotics was registered medical shops and pharmacies. Conclusions: There is an urgent need for public health authorities in India to enforce existing laws on antibiotic sales and enlighten people on the dangers of irrational use of antibiotics.